2013
DOI: 10.1007/s00531-013-0963-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fluid circulation in extensional faults in the central Catalan Coastal Ranges: P–T constraints from neoformed chlorite and K-white mica

Abstract: The neoformation of chlorite and K-white mica in fault rocks from two main faults of the central Catalan Coastal Ranges, the Valle `s and the Hospital faults, has allowed us to constrain the P-T conditions during fault evolution using thermodynamic modeling. Crystallization of M1 and M2 muscovite and microcline occured as result of deuteric alteration during the exhumation of the pluton (290 °C [ T [ 370 °C) in the Permian. After that, three tectonic events have been distinguished. The first tectonic event, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Conversely, chlorite can directly grow as newly formed metamorphic or diagenetic phase, with a composition dictated by the bulk rock composition and mineral equilibria (Lanari et al 2012). It is now well established that the chemical composition of chlorite does also depend on the conditions of formation such as temperature and pressure and can be used for thermobarometric estimates in various geological contexts (Cathelineau and Nieva 1985;Walshe 1986; Kranidiotis and MacLean 1987;Cathelineau 1988;Hillier and Velde 1991;Jowett 1991;de Caritat et al 1993;Zang and Fyfe 1995;Baker and Holland 1996;Vidal and Parra 2000;Vidal et al 2001Vidal et al , 2006Le Hébel et al 2002;Parra et al 2002b;Á rkai et al 2003;de Andrade et al 2006;Yamato et al 2007;Inoue et al 2009Inoue et al , 2010Schwartz et al 2009;Tarantola et al 2009;Plissart et al 2009;Saravanan et al 2009;Verlaguet et al 2011;Ganne et al 2012;Grosch et al 2012;Lacroix et al 2012;Lanari et al 2012;Bourdelle et al 2013a, b;Pourteau et al 2013;Cantarero et al 2013;Lanari et al 2013b). During the last 30 years, three different approaches to chlorite thermometry were developed:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, chlorite can directly grow as newly formed metamorphic or diagenetic phase, with a composition dictated by the bulk rock composition and mineral equilibria (Lanari et al 2012). It is now well established that the chemical composition of chlorite does also depend on the conditions of formation such as temperature and pressure and can be used for thermobarometric estimates in various geological contexts (Cathelineau and Nieva 1985;Walshe 1986; Kranidiotis and MacLean 1987;Cathelineau 1988;Hillier and Velde 1991;Jowett 1991;de Caritat et al 1993;Zang and Fyfe 1995;Baker and Holland 1996;Vidal and Parra 2000;Vidal et al 2001Vidal et al , 2006Le Hébel et al 2002;Parra et al 2002b;Á rkai et al 2003;de Andrade et al 2006;Yamato et al 2007;Inoue et al 2009Inoue et al , 2010Schwartz et al 2009;Tarantola et al 2009;Plissart et al 2009;Saravanan et al 2009;Verlaguet et al 2011;Ganne et al 2012;Grosch et al 2012;Lacroix et al 2012;Lanari et al 2012;Bourdelle et al 2013a, b;Pourteau et al 2013;Cantarero et al 2013;Lanari et al 2013b). During the last 30 years, three different approaches to chlorite thermometry were developed:…”
Section: Introductionmentioning
confidence: 99%
“…Chlorite compositions are modeled using the amesite, clinochlore, daphnite and sudoite end-members (Vidal et al 2001) with an extension to Fe-amesite (fames) in updated versions (Vidal et al 2005(Vidal et al , 2006. These models were successfully applied to metapelites using multi-equilibrium techniques (see e.g., Vidal and Parra 2000;Trotet et al 2001;Parra et al 2002b;Ganne et al 2003Ganne et al , 2012Augier et al 2005a, b;Vidal et al 2006;Rimmelé et al 2006;Yamato et al 2007;Schwartz et al 2009;Lacroix et al 2012;Grosch et al 2012;Lanari et al 2012Lanari et al , 2013bLanari 2012;Pourteau et al 2013;Cantarero et al 2013). However, these models cannot be used for phase diagram computation with the internally consistent thermodynamic data set.…”
Section: Introductionmentioning
confidence: 99%
“…The fault rocks of the Río Grío and Vallès‐Penedès Faults did not yield K‐Ar dates younger than the Eocene, even though Alpine deformation is documented until the Late Miocene for some areas of the Iberian Chain and the Middle Miocene for the Catalan Coastal Range. Sedimentological, structural, and low‐temperature thermochronological studies for the latter range showed that rocks exposed nowadays were deformed at a maximum depth of 3.6 km during the Paleogene compression at a temperature of 110 °C, and they were at depths of about 2 km and temperatures lower than 60 °C prior to the Miocene extension (Anadón et al, ; Cantarero et al, ; Juez‐Larré & Andriessen, ). This may suggest that Late Oligocene‐Miocene deformation in both chains occurred under shallower and/or cooler P‐T conditions than those prevailing during Mesozoic and Eocene times and/or the absence of physicochemical conditions favorable to illite authigenic growth during brittle deformation. Reactivation of fault zones does not necessarily correspond to the timing of the highest temperature thermal event.…”
Section: Discussionmentioning
confidence: 99%
“…This method can be used to estimate P -T conditions of crystallization of K-white mica in various environments (e.g. Lanari et al 2012Lanari et al , 2014Cantarero et al 2014). Si content and XMg isopleths with phengite + quartz + H 2 O equilibria intersect at 525 + 508C and 19 + 2.5 kbar.…”
Section: Pressure -Temperature Conditions Of Sediments Hosting Mafic mentioning
confidence: 99%